Effects of hydrotherapy on balance in the elderly: Systematic review (Research, Society and Development, 2022)
Objective: To evaluate, through a systematic review, the effects of hydrotherapy on the balance of the elderly and its implications for the risk of falling. Methodology: The present study was carried out through a systematic review, following the recommendations of the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). Searches were performed in the following databases: Cochrane, MEDLINE, PUBMED and PEDro. Results: In the identification process, 105 scientific articles were found. Of these, 43 were excluded because they were duplicated in the databases, leaving 62 articles for the selection stage, in which 53 were excluded for not being adequate to the determined criteria. Of the 9 articles selected for analysis, all were considered suitable and were included in the analysis. Most articles found positive effects of the use of hydrotherapy on balance in the elderly. Since the therapies performed in an aquatic environment lead to an improvement in the strength and resistance of the muscles of the extremities, in addition to promoting an improvement in the individuals' motor coordination. Conclusion: Aquatic physiotherapy is effective in developing resistance, strength and, consequently, in increasing balance in elderly patients.